Role of Glutathione Depletion and Reactive Oxygen Species Generation on Caspase-3 Activation: A Study With the Kinase Inhibitor Staurosporine - Musaogullari, Aysenur; Mandato, Alysia; Chai, Yuh-Cherng (Frontiers in Physiology, 2020)
Oxidative stress is known to contribute to the progression of apoptosis. Staurosporine is a broad-spectrum inducer of apoptosis, but its mechanism of action is not well understood. The goal of the present work was to elucidate the role of glutathione and reactive oxygen species in the execution of staurosporine-induced apoptosis. HeLa cells were treated with staurosporine at 1 μM for up to 4 h. The concentration of glutathione, generation of reactive oxygen species, and activation of caspase-3 were measured. The introduction of staurosporine significantly decreased the concentration of cellular glutathione and increased the presence of reactive oxygen species after 3 h. These findings were concurrent with the activation of caspase-3. Interestingly, pre-treatment of cells with N-acetylcysteine, a precursor of glutathione and a thiol antioxidant, failed to block the depletion of glutathione, generation of reactive oxygen species, and activation of caspase-3. Collectively, these results suggest that the cellular redox status may be one of the critical factors of the apoptotic pathway leading to caspase-3 activation by staurosporine.